1. $\displaystyle r = - 3 \sin \theta \Rightarrow r^2 = -3 r \sin \theta$ ......
2. $\displaystyle r \sec \theta = 3 \Rightarrow \frac{r}{\cos \theta} = 3 \Rightarrow r = 3 \cos \theta$. Now use what you've learned from how I did 1.
1. $\displaystyle r = - 3 \sin \theta \Rightarrow r^2 = -3 r \sin \theta$ ......
2. $\displaystyle r \sec \theta = 3 \Rightarrow \frac{r}{\cos \theta} = 3 \Rightarrow r = 3 \cos \theta$. Now use what you've learned from how I did 1.
I had already gotten to where you did in 2. 1 is still troubling me though, so you just multiplied both sides by r?